Preparação e caracterização de filmes finos de PPV contendo grupos doadores e aceptores de elétrons - Soares, Cecília Goncalves [UNIFESP] (2014)
The present work was divided into two steps. The first one, the synthesis of precursor materials for polymerization by the Wessling route of poly(p-phenylene vinylene) (PPV) based materials containing acceptor (cyan) and donors (acetoxy) groups of electrons. The synthesis proved to be satisfactory, due to the obtainment pure products, confirmed by ¹H-NMR and ¹³C-NMR, and with high yields. The syntheses of the polymers were presented molecular weight lower than 12000 Da after process of purification. In the second step, the influence of the dicyano group in a copolymer of PPV, DCNPPV-PPV, was studied as its formation as in Langmuir and Langmuir-Blodgett (LB) film and its incorporation organophilic montmorillonite clay (OMMT). The Langmuir films were obtained from the pure copolymer and these films were compressed to a surface pressure of 45 mN/m without attaining the monolayer collapse. These films were transferred to solid substrates through the Langmuir-Blodgett (LB) technique, forming monolayers with few aggregates and low roughness. The incorporation of the copolymer in organophilic montmorillonite clay (OMMT) was efficient and the fluorescence analysis confirmed the incorporation of the copolymer in all proportions employed. The thermogravimetry analyses showed the thermal protection in the copolymer. In the sample containing 1% of the incorporated copolymer, a greater incorporated percentage was observed and at fluorescence analysis demonstrated a lower formation of excimers and aggregates, suggesting that the polymer chains are located in the lamellar space of the clay.